Top Incomes and Human Well-being Around the World - Richard V. Burkhauser; Jan-Emmanuel De Neve; Nattavudh Powdthavee (Institute for the Study of Labor (IZA), 2016)
The share of income held by the top 1 percent in many countries around the world has been rising persistently over the last 30 years. But we continue to know little about how the rising top income shares affect human well-being. This study combines the latest data to examine the relationship between top income share and different dimensions of subjective well-being. We find top income shares to be significantly correlated with lower life evaluation and higher levels of negative emotional well-being, but not positive emotional well-being. The results are robust to household income, individual's socio-economic status, and macroeconomic environment controls.
Keywords: D63; I3; 330; top income; life evaluation; well-being; income inequality; World Top Income Database; Gallup World Poll